USE OF RUBBER WASTE TO MODIFY THE BINDER IN ASPHALT CONCRETE (American Journal of Interdisciplinary Research and Development, 2024)
The development and implementation of road surfaces resistant to temperature extremes and high technogenic loads is one of the important tasks for road workers. These surfaces must be economically viable for production. Since the known methods for improving the physicomechanical properties of a binder for asphalt concrete involve the introduction of expensive foreign polymers. Rubber crumb, being a waste of production, allows to solve the problem with the disposal of used tires, and the cost of such a modifier for road bitumen is lower than foreign polymers. The article describes an example of using a rubber crumb to modify the road binder in asphalt concrete. The compositions of bitumen-rubber suspensions, the determination of the physicomechanical properties of a modified binder are described. The test results of asphalt concrete with a bitumen-rubber binder are given. A comparative analysis of asphalt concrete on bitumen oil road viscous and asphalt concrete on a modified binder is carried out. The purpose of this work is to develop a theoretical justification and practical application of a bituminous-rubber binder obtained by combining oil road bitumencomposite surpasses viscous petroleum bitumen in physical and mechanical properties and is suitable for use as a binder for the production of high-quality asphalt concrete.